Pengaruh Komitmen Organisasi, Lingkungan Kerja, dan Motivasi terhadap Organizational Citizenship Behavior (OCB) Karyawan PT Sport Glove Indonesia Cabang Wonosari - Lathifah Piyandini; Hari Nurweni; Retno Hartati (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2020)
Organizational goals can be achieved with the helps of Organizational Citizenship Behavior (OCB). Internal and external factors can influence OCB. Research aims to seek the effects of organizational commitment, work environment, and motivation on OCB on employees of PT Sport Glove Indonesia Wonosari branch. The research was conducted in November 2019 at PT Sport Glove Indonesia Wonosari branch. The research approach is quantitative. Data collection using questionnaires. All employees of the Needle Machine Production Section, PT Sport Glove Indonesia Wonosari branch as the population of this research. Non probability sampling techniques using census method is used to take the samples. A total of 48 employees of all employees of the Needle Machine Production Section, PT. Sport Glove Indonesia, Wonosari Branch participated as a respondent. Multiple linear regression technique is used to analize the data. The results of the research showed the organization’s commitment and work environment had no effect on OCB, while the motivation had a positive and significant impact on OCB. The benefits of this study add literature on the effects of organizational commitment, work environment, and motivation on OCB